Visual mechanisms of motion analysis and motion perception - Derrington, Andrew; Allen, Harriet A.; Delicato, Louise (Annual Reviews, 2003)
Psychophysical experiments on feature tracking suggest that most of our sensitivity to chromatic motion and to second-order motion depends on feature tracking. There is no reason to suppose that the visual system contains motion sensors dedicated to the analysis of second-order motion. Current psychophysical and physio- logical data indicate that local motion sensors are selective for orientation and spatial frequency but they do not eliminate any of the three main models—the Reichardt de- tector, the motion-energy filter, and gradient-based sensors. Both psychophysical and physiological data suggest that both broadly oriented and narrowly oriented motion sensors are important in the early analysis of motion in two dimensions.